Langerhans cell histiocytosis following Hodgkin lymphoma: A case report from Iran - Nahid Reisi Dehkordi; Parvin Rajabi; Azar Naimi; Mitra Heidarpour (Journal of Research in Medical Sciences, 2010)
The occurrence of Langerhans Cell Histiocytosis (LCH) in a patient with lymphoma is an indication of a probable relationship between them. The two conditions have similarities both clinically and histopathologically. Occurrence of these two conditions in the same patient, particularly not simultaneously, is rare. According to different management and treatment of these conditions, exact histopathologic evaluation and even using immunohistochemistery (IHC) can prevent misdiagnosis. In this report, a 10 year old boy presented who afflicted with LCH 3 years after diagnosis and treatment of mixed cellularity Hodgkin lymphoma.